Hospitalizations, emergency medical care utilization, and contacts with the regional on-call medical services among nursing home residents in Germany: a cross-sectional study in 44 nursing homes - Paula Lienesch; Heinz Rothgang; Ansgar Gerhardus; Karin Wolf-Ostermann; Falk Hoffmann; Jonas Czwikla (BMC Health Services Research)
Abstract Background Nursing home residents frequently utilize medical care, but there lacks a complete picture of their acute medical care utilization. We quantified hospitalizations, emergency medical care utilization, and contacts with the regional on-call medical services among nursing home residents, and investigated individual characteristics that may be associated with the utilization of these medical care types. Methods Cross-sectional data from the “Needs-based provision of medical care to nursing home residents” (MVP-STAT) study were analyzed, which were collected in 44 German nursing homes from 442 residents in 2018/2019. Proportions of residents with at least one hospitalization, emergency medical care utilization (via the nationwide phone number 112), and contact with an on-call medical service (nationwide via 116117) over the previous 12 months were determined. Associations between individual characteristics and the utilization of the three medical care types were examined using multivariable logistic regressions. Results Of the analyzed residents, 45.8% were hospitalized, 23.2% utilized emergency medical care, and 12.1% had contact with an on-call medical service at least once in the previous 12 months. Hospitalizations were positively associated with male vs. female sex (adjusted odds ratio 1.99 [95% confidence interval 1.22–3.26]), age group 85 + vs. 60–74 years (2.15 [1.12–4.13]), long-term care grades 4/5 vs. 1/2 (2.78 [1.48–5.21]), 6 + vs. 0–1 Elixhauser diseases (2.58 [1.01–6.62]), and the risk or presence of vs. no malnutrition (3.10 [1.52–6.35] and 2.01 [1.26–3.21]); and not associated with years of residence in the respective nursing home. Emergency medical care utilization was positively associated with age group 85 + vs. 60–74 years (2.58 [1.14–5.84]) and long-term care grades 3 and 4/5 vs. 1/2 (2.65 [1.07–6.55], 6.31 [2.60–15.35]); negatively associated with 5 + vs. 1- < 3 years of residence (0.46 [0.24–0.86]); and not associated with sex, the number of Elixhauser diseases, and nutritional status. No associations were found with on-call medical services. Conclusions Hospitalizations and emergency medical care utilization were more frequent among nursing home residents than contacts with on-call medical services. Future studies should investigate whether the frequent hospitalizations and emergency medical care utilization among nursing home residents are justified, or whether they can be reduced by strengthening medical care provision by on-call doctors and other professionals. Trial registration DRKS00012383 [2017/12/06].